Design and analysis of nozzles for pneumatic windshield wiper. Issue 1 (March 2021) - Sur, Anirban; Solke, Nitin; Pandiya, Sharnil; Kotecha, Ketan
Abstract: Almost all the vehicles use mechanical wipers to clean the windscreen when rain or other elements such as dirt hit the surface of the windshield. This helps maintain visibility so the driver can see through the windshield. Also, mechanical wipers can damage the windscreen over time with friction and partially hinder the visibility as they only clear the screen partially. There are no alternative models currently available for solving the same problem. This paper proposes an air jet windshield wiper system consists of a high-speed air outlet mounted on the edge of the windshield through which a high-speed mass of air, called as air-beam, is released over the windshield. This can be achieved with the help of an air nozzle. The air-beam ejected by the outlet of the nozzle is designed to cover most of the surface of the windshield. The beam thickness is used to push rain drops over the windshield to the roof of the vehicle and beyond. In this paper, necessary calculations were done for selecting suitable nozzles for the project. To verify the results, FEM analysis and experimental analysis has been done.